Pengaruh Teknik Pembekuan Ikan Tongkol (Euthynnus affinis) Terhadap Organoleptik di PT. Aceh Lampulo Jaya Bahari - Ifan Muliadi; Anhar Rozi; Afdhal Fuadi (Publikasi Indonesia, 2023)
Tuna contains high protein so that it fulfills the nutritional needs of the human body. Tuna is a marine fish that contains omega 3, vitamins, protein and minerals. This study aims to determine the effect of the freezing technique of tuna (Euthynnus affinis) on organoleptic at PT.Aceh Lampulo Jaya Bahari using a temperature of -30oC to -40oC with a freezing time of about 8 - 12 hours. Methods This study used a qualitative method consisting of research on the first with the influence of the technique of freezing tuna (Euthynnus affinis) with a comparison of 3 freezing methods, the second stage carried out an organoleptic analysis (ice layer, dehydration, discoloration, appearance, smell, texture.) on frozen tuna. The results of the value of the ice layer showed that the most preferred value by the analyst was the value of the semi contact plate freezer 7 ± 0.67 and cold storage 7 ± 0.67, the dehydration indicated the value most preferred by the analyst was the value of the semi contact plate freezer 7 ± 0.67 and cold storage 7 ± 0.67. The result of the value of dehydration shows the value most preferred by the analyst is the value of the semi contact plate freezer 7 ± 0.78. The result of the value of the appearance shows the value most preferred by the analyst is the value of air blast freezer 7 ± 0.50. the result of the value of the appearance shows the most preferred value by the analyst is the value of the air blast freezer 7 ± 0.50, the result of the value of the odor shows the most preferred value by the analyst is the value of the semi contact plate freezer 7 ± 0.41 and cold storage 7 ± 0.41, the value of the texture shows the most preferred value by the analyst is the value of air blast freezer 7 ± 0.25, semi contact plate freezer 7 ± 0.25 and cold storage 7 ± 0.25.